The Berenstain bears$1 (Btrouble at school s - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1986)
When Brother Bear returns to school after being out sick, he gets into a mess that gets worse and worse until Gramps gives him some advice.
Keywords: Bears -- Fiction; Schools -- Fiction